Systematic review of the cost-effectiveness of sample size maintenance programs in studies involving postal questionnaires reveals insufficient economic information - David, M.; Bensink, M.; Higashi, H.; Boyd, Roslyn; Williams, L.; Ware, R. (2012)
Objectives: To identify and assess the existing cost-effectiveness evidence for sample size maintenance programs. Study Design and Setting: Articles were identified by searching Cochrane Central Register of Controlled Trials Embase, CINAHL, PubMed, and Web of Science from 1966 to July 2011. Randomized controlled trials in which investigators evaluated program cost-effectiveness in postal questionnaires were eligible for inclusion. Results: Fourteen studies from 13 articles, with 11,165 participants met the inclusion criteria. Thirty-one distinct programs were identified; each incorporated at least one strategy (reminders, incentives, modified questionnaires, or types of postage) aimed at minimizing attrition. Reminders, in the form of replacement questionnaires and cards, were the most commonly used strategies, with 15 and 11 studies reporting their usage, respectively. All strategies improved response, with financial incentives being the most costly. Heterogeneity between studies was too great to allow for meta-analysis of the results. Conclusions: The implementation of strategies such as no-obligation incentives, modified questionnaires, and personalized reply paid postage improved program cost-effectiveness. Analyses of attrition minimization programs need to consider both cost and effect in their evaluation. © 2012 Elsevier Inc. All rights reserved.